1992
DOI: 10.1093/ajh/5.11.781
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Maximal Vasodilatory Capacity of Forearm Resistance Vessels in Normotensive Young Adults

Abstract: This study was performed to determine whether alterations in vascular structure exist in a biracial population of young (age 22.3 +/- 0.6 yrs [mean + SE]) normotensive men. We examined maximal vasodilatory capacity in 21 blacks and 20 whites (average blood pressure = 122/75 and 118/72 mm Hg, respectively). Forearm blood flow was determined at rest and after 10 min of ischemic handgrip exercise using venous occlusion plethysmography. Forearm vascular resistance was computed from blood flow and mean arterial blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
3
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 0 publications
2
34
3
4
Order By: Relevance
“…For example, exerciseinduced, 5 ischemia-induced, 20 and mental stress-induced 7 forearm vasodilation were reported to be lower in healthy black subjects compared with healthy white subjects. Lang and colleagues observed lower forearm blood flow responses to intra-arterial isoproterenol infusion in healthy black men compared with white men.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, exerciseinduced, 5 ischemia-induced, 20 and mental stress-induced 7 forearm vasodilation were reported to be lower in healthy black subjects compared with healthy white subjects. Lang and colleagues observed lower forearm blood flow responses to intra-arterial isoproterenol infusion in healthy black men compared with white men.…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies have demonstrated impaired vascular function in forearm resistance vessels of healthy young black subjects compared with whites. [5][6][7][8] These differences are likely to be clinically important because endothelium-derived nitric oxide plays a major role in vascular homeostasis via its effects as a vasodilator and as an inhibitor of platelet activity, monocyte adhesion, and smooth muscle proliferation. 9 Furthermore, recent studies have demonstrated that impaired endothelial function in the microvasculature is predictive of future cardiovascular disease events.…”
mentioning
confidence: 99%
“…O fenótipo vascular favorecendo a HAS mais grave no negro pode ser melhor compreendido através da avaliação farmacológica de substâncias vasoativas na microcirculação. O efeito vasodilatador atenuado do isoproterenol (agonista β 2 ), sobretudo no negro hipertenso, inclusive com facilitação da vasoconstrição noradrenérgica, fala a favor de polimorfismo racial no receptor adrenérgico β que pode contribuir na fisiopatologia da insuficiência cardíaca [39][40][41][42][43] .Além de mecanismos não adrenérgicos (renina reduzida, hipernatremia, vasopressina etc. ), o aumento da reatividade simpática no negro americano contribui para o desenvolvimento da HAS.…”
Section: Iii) Sistema Vascularunclassified
“…O hipertenso com insuficiência cardíaca de diferentes raças responde favoravelmente à administração do bloqueador α e β como o carvedilol, podendo ser associado ou não a antagonistas de canais lentos de cálcio ou a uma terapêutica diuréti-ca 3, 54,55 . O alelo polimorfo T do gen C825T do unidade β 3 da proteína G facilita a excreção renal de Na + /H + em resposta à manoterapia com diurético benzotiazídico em negros hipertensos com baixo nível de renina 38,39 . O manejo farmacológi-co adequado da HAS deve levar em conta as diferenças raciais em sua fisiopatologia.…”
Section: Iii) Sistema Vascularunclassified
See 1 more Smart Citation